Principle of responsibility in the Medina charter to build cooperative relations of the cross-cultural community - Zaleha Embong,; Amaal Fadhlini Mohamed,; Nazri Muslim,; Noor Shakirah Mat Akhir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Medina Charter is the world’s first written constitution enacted by the Prophet Muhammad PBUH to manage the cross-cultural society in Yathrib (after the migration, Yathrib changed its name to Medina al-Munawwarah). The Yathrib community comprises of various ethnicities, languages, religions, and tribes. Before the arrival of Islam, Yathrib had no organised political system and people lived in factions and sects. Its people were constantly in conflict due to high levels of ethnocentrism, fight instigations and quarrels of merely small matters. Thus, the Prophet PBUH drafted the Medina Charter to build cooperative relations within the cross-cultural society. This article aims to identify the principles of responsibility in the Constitution of Medina and analyse the principles of responsibility in building cooperative relationships of cross-cultural communities in Medina. Qualitative methods i.e., in-depth interviews and (systematic) literature review or library research were used for this study. In analysing the data, content analysis method was employed. The results found that this Charter has laid down the principle of responsibility to be followed by every individual for the common good and has succeeded in uniting and fostering cooperative relations within the cross-cultural community of Medina.